Redefinition of the genus Luciaphorus Mahunka, 1981 (Acari: Pygmephoridae) with redescription of L. perniciosus Rack, 1983 and L. auriculariae Gao, Zou and Jiang, 1990 - Khaustov, Alexander A.; Shentu, Hsuan; Ho, Chyi-Chen (Zootaxa, 2018)
The genus Luciaphorus Mahunka, 1981 (Acari: Pygmephoridae) is redefined. Two species, Luciaphorus auriculariae Gao, Zou and Jiang, 1990 and L. perniciosus Rack, 1983 are redescribed based on materials collected on cultivated cloud-ear fungus, Auricularia polytricha, in Taiwan. The taxonomic position of the genus Luciaphorus is discussed. A key to Luciaphorus species is provided.